Constraints and Legal Efforts for Consumer Protection in Overcoming Forced Withdrawals by Leasing Parties in Fiduciary Guarantees - Dandi Nugraha Fadilah; Fakhlur Fakhlur (Fakultas Hukum Dehasen, 2022)
Fiduciary guarantee is a guarantee right on movable objects, both tangible and intangible and immovable objects, especially buildings that cannot be encumbered with mortgage rights as referred to in Law Number 4 of 1996 concerning Mortgage Rights that remain in the control of the Fiduciary Giver, as collateral for repayment of certain debts, which gives priority to the Fiduciary Recipient over other creditors. The procedure for carrying out the execution of objects that are the object of a fiduciary guarantee must really fulfill completely and perfectly as has been determined, both in Article 29, Article 30, and Article 31 of the Fiduciary Guarantee Law. If it is done deviating or contrary to the intent and purpose of the provisions regarding the execution of this fiduciary guarantee, then the execution of the object that is the object of the fiduciary guarantee is null and void by law. The purpose of this research is to analyze and find out how the constraints and legal remedies for consumer protection in overcoming forced withdrawals by leasing parties in fiduciary guarantees. This study uses a sociological juridical approach, with analytical descriptive research methods. The data used are primary and secondary data which will be analyzed qualitatively. The results of the study concluded that the use of Fiduciary Security still has several obstacles including: 1). Fiduciary Guarantee Registration. 2). Guaranteed vehicle withdrawals. 3). Elimination of Fiduciary Guarantee after the debt has been repaid. Consumer protection against forced withdrawals in fiduciary guarantees in the future should continue to be consistent with Law Number 8 of 1999 concerning Consumer Protection (UUPK). The enactment of this Law provides hope for the people of Indonesia, to obtain protection for losses suffered on transactions of goods and services. UUPK guarantees legal certainty for consumers.